Growth, yield and quality of tomatoes (Lycopersicon Esculentum Mill.)and lettuce (Lactuca Sativa L.) as affected by gel-polymer soil amendment and irrigation management - Soundy, Puffy (University of Pretoria, 2013)
Dissertation (MSc (Horticulture))--University of Pretoria, 2005.